2015
DOI: 10.1177/1524839915616362
|View full text |Cite
|
Sign up to set email alerts
|

Training in Patient Navigation

Abstract: Despite the proliferation of patient navigation programs designed to increase timely receipt of health care, little is known about the content and delivery of patient navigation training, or best practices in this arena. The current study begins to address these gaps in understanding, as it is the first study to comprehensively review descriptions of patient navigation training in the peer-reviewed research literature. Seventy-five patient navigation efficacy studies published since 1995, identified through Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 92 publications
(43 reference statements)
0
38
1
Order By: Relevance
“…There is little evidence on the optimum length, mode or content of training programmes for peer mentors or other similar patient facing volunteers. Recent reviews have variously reported no trials in the area of volunteer training for those in palliative care roles [16] and little information on the training of peer supporters [9] and variation in duration, location, format, learning strategies employed and occupation of trainer and content of training reported in included studies [44]. Training typically takes place on more than 1 day, with a varied focus on organizational content (understanding the service to be provided, personal safety, lone working arrangements, safeguarding, etc.…”
Section: Peer Mentor Trainingmentioning
confidence: 99%
“…There is little evidence on the optimum length, mode or content of training programmes for peer mentors or other similar patient facing volunteers. Recent reviews have variously reported no trials in the area of volunteer training for those in palliative care roles [16] and little information on the training of peer supporters [9] and variation in duration, location, format, learning strategies employed and occupation of trainer and content of training reported in included studies [44]. Training typically takes place on more than 1 day, with a varied focus on organizational content (understanding the service to be provided, personal safety, lone working arrangements, safeguarding, etc.…”
Section: Peer Mentor Trainingmentioning
confidence: 99%
“…28 Similar to the rapid review, a recent review of patient navigation research found that nationwide, training content is inconsistent, with considerable differences noted in training components, duration, location, format, learning strategies, trainers' skills and knowledge, and program content. 5 To ensure that individuals acquire the knowledge and skills relevant to patient navigation, it is imperative that training be based on a consensus set of minimum core competencies connected to quality standards and that metrics be established. Such core competencies should articulate a patient navigation skill set that transcends the degree or type of clinical training.…”
Section: Discussionmentioning
confidence: 99%
“…In the research literature, patient navigation training was mentioned, but it lacked Cancer December 15, 2019 details about educational components. 5 Subsequently, the cochairs discussed issues with the task group members and used the internet as a source for identifying patient navigation training program details. Search terms included patient navigation, community health worker, lay and clinical, competencies, training, and education.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations